2020
DOI: 10.1002/ece3.6536
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal trend in the reproductive mode of the pea aphid Acyrthosiphon pisum invading a wide climatic range

Abstract: The maintenance of sexuality is a puzzling phenomenon in evolutionary biology. Many universal hypotheses have been proposed to explain the prevalence of sex despite its costs, but it has been hypothesized that sex could be also retained by lineage‐specific mechanisms that would confer some short‐term advantage. Aphids are good models to study the maintenance of sex because they exhibit coexistence of both sexual and asexual populations within the same species and because they invade a large variety of ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…96%, respectively). However, aphid MLGs were not comparable with the ones found by Peccoud et al [23] because of some distinctive microsatellite markers and a different capillary sequencer used for this work (see Material and Methods section in Martel et al [47]).…”
Section: Introductioncontrasting
confidence: 56%
See 3 more Smart Citations
“…96%, respectively). However, aphid MLGs were not comparable with the ones found by Peccoud et al [23] because of some distinctive microsatellite markers and a different capillary sequencer used for this work (see Material and Methods section in Martel et al [47]).…”
Section: Introductioncontrasting
confidence: 56%
“…These findings suggest the coexistence of different clonal lineages, considering that the main transmission mechanism for the secondary symbionts in aphids is maternal inheritance and that the pea aphid population of central Chile has shown to be strictly asexual [23,46]. (iii) In a more recent work, Martel et al [47] found not only one but two different MLGs in the same latitudinal range (APG2 and APG3) but in quite different proportions (approx. 4% and approx.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The lack of both recombination and independent assortment of heritable elements, will complicate efforts to pinpoint targets of selection, a problem extending to maternally inherited symbionts of such asexuals [ 108 ]. Pea aphids show a mixture of sexual and asexual reproduction throughout varying parts of their range, e.g., [ 109 ]. As such, portions of some populations may survive presumably mild winter seasons as asexual, parthenogenetic morphs, instead of overwintering as cold-tolerant eggs produced by matings between male and female sexual morphs.…”
Section: Methodsmentioning
confidence: 99%